1998
DOI: 10.3739/rikusui.59.281
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in C, N and P of the Periphyton on the Tropical Aquatic Macrophyte Echinochloa polystachya (H.B.K.) HITCH. in Jurumirim Reservoir (São Paulo, Brazil)

Abstract: The temporal variations in C, N and P concentrations of the periphyton on the natural substratum (Echinochloa polystachya) and its relationships to the water's climatological (air temperature and precipitation), hydrodynamic (water discharge and water level), physical (temperature, transparency) and chemical variables (conductivity, total suspended solids, nitrate, nitrite, ammonia, silica, total phosphorus and orthophosphate)were evaluated in a lagoon at the Paranapanema River mouth into the Jurumirim Reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
1
2

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
1
0
1
2
Order By: Relevance
“…According to the authors, the remainder of the carbon in the periphyton was due to the production of mucilage and other organic materials by bacteria and algae. Moschini-Carlos et al (1998) and Guariento et al (2011) measured average concentrations of carbon in the periphytic biomass that were higher than those found in the present study. One possible explanation for this fact might be the different types of substrate colonisation of periphyton, as was observed by Zebek (2009).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…According to the authors, the remainder of the carbon in the periphyton was due to the production of mucilage and other organic materials by bacteria and algae. Moschini-Carlos et al (1998) and Guariento et al (2011) measured average concentrations of carbon in the periphytic biomass that were higher than those found in the present study. One possible explanation for this fact might be the different types of substrate colonisation of periphyton, as was observed by Zebek (2009).…”
Section: Discussioncontrasting
confidence: 90%
“…The concentrations of carbon and nitrogen in the periphytic community also showed strong correlations with nitrate concentrations. In a study of the Jurumirim reservoir (São Paulo State, Brazil), Moschini-Carlos et al (1998) also found positive relationships between the elemental composition of the periphyton and the hydrological regime, which supports our hypothesis.…”
Section: Discussionsupporting
confidence: 87%
“…Assim, a variação da composição específi ca ou da densidade do fi toplâncton nesses lagos está associada, geralmente, a fatores locais (Esteves 1998). Moschini-Carlos et al (1998), observaram que as concentrações mais elevadas de nutrientes numa lagoa próximo ao rio Paranapanema, SP, foi durante o período de seca, considerando as variações no nível d'água como um dos fatores determinantes. A biomassa fi toplanctônica, em termos de clorofi la a, apresentou uma menor concentração nos meses de abril e setembro de 2008, ambos no ponto 1 (0,3 μg.L -1 ) e a maior concentração de clorofi la a ocorreu no mês de junho de 2008 com 8,5 μg.L -1 (ponto 1) (Tab.…”
Section: Resultsunclassified
“…Esta comunidade é caracterizada também pela habilidade em responder às mudanças ambientais e disponibilidade de nutrientes nos diversos ecossistemas aquáticos (Moschini-Carlos et al, 1998), principalmente nitrogênio e fósforo.…”
Section: Introductionunclassified